Investigation into magnetic drive sealless pump failure 3 flare gas recovery unit (FGRU) - Yahya, M Farid; Ab Malek, Muhammad Faiz; Mat Dan, Reduan (Universiti Teknologi Petronas, 2023)
Failure investigation was conducted on magnetic drive centrifugal sealless pumps that had only been operating for six months and were already struggling to rotate. It was discovered that hydrocarbon sludge and other debris had blocked the lubricating channel, which was meant to provide pathways for cooling and lubricating the pump's inner magnetic and containment shell. Further investigation revealed that service water had contaminated the process fluid, precipitating calcium carbonate upon contact with the amine solution and clogging the flushing line. An additional duplex strainer was installed on the repaired pumps, and adequate precautions were taken to prevent water contamination.